Analyzing the Impact of China-Russia Relations and Market Demands on Forest Product Trade: Implications for Resource Management in Sports Infrastructure - Xiaomin Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
China and Russia have obvious geographical advantages, strong economic strength and rapid development of forest product trade. China is short of forest resources, and the consumption of wood forest products is growing rapidly. This makes the supply of wood forest products more and more dependent on imports, and the trade of forest products between the two countries becomes more and more important. China Russia international relations and changes in demand will have a greater impact on China-Russia forest product trade. How to evaluate the impact of China-Russian international relations and demand changes on the fluctuation of forest product trade has become an important topic. This work designs an artificial intelligence method to finish this task. First, this work improves the traditional AFSA algorithm to construct IAFSA. Its improvement measures mainly include the improvement of step size, field of view and behavior selection. Second, in view of the shortcoming that BP network is easy to fall into local optimal solution, this work uses IAFSA to improve it to construct IAFSA-BP network. Third, this work applies the IAFSA-BP algorithm to evaluate the impact of China-Russian international relations and demand changes on the fluctuation of forest product trade. Fourth, this work carried out systematic experiments on the designed IAFSA-BP method, and the experimental results fully verified the feasibility of the method.